Hide, keep quiet, and keep low: properties that make Aspergillus fumigatus a successful lung pathogen - Natalia eEscobar; Soledad R Ordonez; Han eWösten; Pieter-Jan eHaas; Hans ede Cock; Henk Peter Haagsman (Frontiers in Microbiology, 2016)
Representatives of the genus Aspergillus are opportunistic fungal pathogens. Their conidia can reach the alveoli by inhalation and can give rise to infections in immunocompromised individuals. Aspergillus fumigatus is the causal agent of invasive aspergillosis in nearly 90 % of the cases. It is not yet well established what makes this fungus more pathogenic than other aspergilli such as Aspergillus niger. Here, we show that A. fumigatus and A. niger conidia adhere with similar efficiency to lung epithelial A549 cells but A. fumigatus conidia internalized 17% more efficiently. Conidia of both aspergilli were taken up in phagolysosomes 8 h after the challenge. These organelles only acidified in the case of A. niger, which is probably due to the type of melanin coating of the conidia. Viability of both types of conidia was not affected after uptake in the phagolysosomes. Germination of A. fumigatus and A. niger conidia in the presence of epithelial cells was delayed when compared to conidia in the medium. However, germination of A. niger conidia was still higher than that of A. fumigatus 10 h after exposure to A549 cells. Remarkably, A. fumigatus hyphae grew mainly parallel to the epithelium, while growth direction of A. niger hyphae was predominantly perpendicular to the plane of the cells. Neutrophils reduced germination and hyphal growth of A. niger, but not of A fumigatus, in presence of epithelial cells. Taken together, efficient internalization, delayed germination, and hyphal growth parallel to the epithelium gives a new insight into what could be the causes for the success of A. fumigatus compared to A. niger as an opportunistic pathogen in the lung.